(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
For secure and smart transactions over open networks, the Digital Signature Concept is necessary. It is having forms of programs with a view to make certain the integrity of information exchanged or saved and to show the identity of the originator to the recipient. Digital Signature techniques are usually used in cryptographic protocols to provide services like entity authentication, authenticated key delivery and authenticated key agreement. With using cellular devices as a client of internet, the risk of unauthorized and unauthenticated get admission to of crucial files (e.g. contracts, receipts, and so forth.) is growing every day. Although Digital Signature is supposed to be the solution for the unauthorized get right of entry to, its implementation isn’t always good enough till now. The symmetric records transfer mechanism is used for the transfer of essential documents, but there’s a want of a greater ready mechanism for safe transfer and verification of the documents. This Research paper presents a comprehensive study of Digital Signature and its benefits.